Marc Epprecht, Welcome to Greater Edendale: Histories of Environment, Health, and Gender in an African City (Historia, 2021)
Marc Epprecht examines South Africa’s unsettling continuities between pre-colonial, colonial, apartheid, and post-apartheid policies in an attempt to reconstruct the country’s environmental history. The author hints that the themes referenced in thesubtitle are key to the historical narrative. Thus, he studies contestation over land, housing, sanitation, public health, and the meaning of development in Pietermaritzburg, KwaZulu-Natal. The book is divided into seven chapters. The first introduces key theoretical concepts and chapter outlines. The second and third make gestures towards the goal of decolonising knowledge about Msunduzi. These chapters show how the local environment has been seriously misrepresented and used for political purposes in the process of reconstructing the eco-health history of the city. The fourth critiques Maynard Swanson's theory of sanitation syndrome in the historiography of African cities using the “native village” debate of Pietermaritzburg as a case study. The fifth and sixth chapters are devoted to an investigation of colonial development interventions in Edendale through a close examination of some key decisions that ultimately led to the abandonment of the liberal promise in favour of so-called separate development and racial zoning. The concluding chapter documents industrialisation, environmental activism and health from the period of apartheid to democracy in South Africa. This book will certainly be regarded as a classic in the literature on Greater Edendale.
Keywords: Marc Epprecht; South Africa; KwaZulu-Natal; eco-health; European